A novel magnetic NiFe2O4@graphene–Pd multifunctional nanocomposite for practical catalytic application1. Issue 97 (21st October 2015) - Zhao, Xiaohua; Liu, Xiang
<x xml:space="preserve">Abstract</x> A novel NiFe2O4@GN–Pd was used as outstanding catalyst for the Suzuki reaction in EtOH/H2O. The hybrid catalyst could be recycled and reused with the simple application of an external magnetic field, while keeping similar catalytic activity for six successive reactions.